Engineering analysis : interactive methods and programs with FORTRAN, QuickBASIC, MATLAB, and Mathematica /: interactive methods and programs with FORTRAN, QuickBASIC, MATLAB, and Mathematica. ([2019?]) - Pao, Y. C
No abstract available